Sustainable Supplier Selection and Order allocation using Integrating AHP-TOPSIS and Goal Programming - Thomy Eko Saputro; Zida Heilmalia Aqiel Melita Khusna; Shanty Kusuma Dewi (Jurnal Teknik Industri, 2023)
Increased awareness of environmental and social aspects has become an urgent global issue, especially in ensuring supply chain sustainability. In addition, optimizing sustainable supplier selection and order allocation is also crucial for companies to encourage sustainable industries. This research aims to determine the best potential sustainable suppliers and determine order allocation by considering economic, social, and environmental dimensions. This research proposes an approach that integrates AHP-Topsis and goal programming to solve the problem of sustainable supplier selection and order allocation. The AHP-Topsis procedure is proposed for weighting the criteria and sub-criteria of sustainable supplier selection. Meanwhile, Topsis is offered for supplier ranking. This study offers a goal programming procedure for order allocation. Order allocation is based on three goals: minimizing total procurement cost, maximizing total purchase value, and reducing carbon emissions. A case study is presented on the plastic bean processing industry in Indonesia involving three criteria (Economic, social, and environmental) and 17 sub-criteria. The analysis results show that economic criteria have the highest weight, followed by environmental and social criteria. Furthermore, the TOPSIS method selected the three best suppliers out of 5 alternative suppliers to receive order allocation. The order allocation process for three periods was carried out using the Goal Programming method on suppliers C, E, and A. This research contributes to improving supply chain sustainability. It provides practical guidance for companies in selecting suppliers and allocating orders efficiently.